A constructivist theoretical proposition of cultural competence development in nursing. (November 2015) - Blanchet Garneau, Amélie; Pepin, Jacinthe
Summary Cultural competence development in healthcare professions is considered an essential condition to promote quality and equity in healthcare. Even if cultural competence has been recognized as continuous, evolutionary, dynamic, and developmental by most researchers, current models of cultural competence fail to present developmental levels of this competence. These models have also been criticized for their essentialist perspective of culture and their limited application to competency-based approach programs. To our knowledge, there have been no published studies, from a constructivist perspective, of the processes involved in the development of cultural competence among nurses and undergraduate student nurses. The purpose of this study was to develop a theoretical proposition of cultural competence development in nursing from a constructivist perspective. We used a grounded theory design to study cultural competence development among nurses and student nurses in a healthcare center located in a culturally diverse urban area. Data collection involved participant observation and semi-structured interviews with 24 participants (13 nurses and 11 students) working in three community health settings. The core category, 'learning to bring the different realities together to provide effective care in a culturally diverse context', was constructed using inductive qualitative data analysis. This core category encompasses three dimensions of cultural competence: 'building a relationship with the other', 'working outside the usual practice framework', and 'reinventing practice in action.' The resulting model describes the concurrent evolution of these three dimensions at three different levels of cultural competence development. This study reveals that clinical experience and interactions between students or nurses and their environment both contribute significantly to cultural competence development. The resulting theoretical proposition of cultural competence development could be used not only to guide initial and continuing nursing education, but also to help redefine quality of care in a culturally diverse context.